2016
DOI: 10.32890/jict2017.16.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Cloud Computing Adoption in Small Medium Enterprises

Abstract: Cloud computing offers information technology (IT) infrastructure, platform, and various applications via the Internet with minimum start-up cost, network access to a shared pool of configurable computing resources, and pay-per-use services.Although the potential for cloud computing is evident and much of the extant research has been carried out on cloud computing adoption, empirical studies on the factors that influence cloud computing adoption in the Malaysian Small and Medium Enterprises (SMEs) are, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
2
25
0
4
Order By: Relevance
“…Thus, the H 0 was rejected. The result seemed to accord with findings by Hassan et al (2017) where SMEs with additional resources projected for the information technology (IT) and are under pressure from the competitors tend to adopt cloud computing. This showed that sales turnover is one of the factors that influenced the intention of the organization to adopt new technology.…”
Section: Association Between Firmographic Profiles and Agrofood Smes'supporting
confidence: 75%
“…Thus, the H 0 was rejected. The result seemed to accord with findings by Hassan et al (2017) where SMEs with additional resources projected for the information technology (IT) and are under pressure from the competitors tend to adopt cloud computing. This showed that sales turnover is one of the factors that influenced the intention of the organization to adopt new technology.…”
Section: Association Between Firmographic Profiles and Agrofood Smes'supporting
confidence: 75%
“…Top management support is as a result of the fact that the conviction and willingness of top management to endorse adequate financial resources, technological competencies and human resources is vital for facilitating successful CC adoption (Hassan et al, 2017). Top management will be motivated to ensure that all kinds of resources needed to adopt CC successfully or expand its usage are provided when they are aware of its benefits (Oliveira et al, 2014;Pathan et al, 2017).…”
Section: Top Management Support On Change Management (Tmscm)mentioning
confidence: 99%
“…Although, Malaysian government has supported SMEs from both financial and non-financial aspects, this study chooses government financial support because Malaysian government has provided huge financial support for CC adoption by SMEs and the effect is yet to be categorically explored. For instance, through the Multimedia Development Corporation (MDeC) Malaysia, government of Malaysia offered a six-month refund on the subscription or RM1,500 and below of the total subscription for any type of SaaS such as cloud ERP from one of the Malaysia Multimedia Super Corridor (MSC) grade firms (Hassan, 2017;Hassan et al, 2017). An annual incentives of 250 USD was also introduced by the CC adoption programme initiated by the Malaysian government to incentivize local SMEs to embrace SaaS business cloud applications such as enterprise resource management (ERP), customer relationship management (CRM), content management systems (CMS) etc., rendered by local SaaS vendors (Rosen et al, 2015).…”
Section: Government Financial Support (Gfs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since cloud computing technology lays its foundation on internet technologies, persistent security issues hurdle its adoption. However, price minimization and modern safety algorithms with information technologies (IT) willingness hired in cloud computing are termed as major distinguishing factors of cloud computing [54] which will influence its adoption. Likewise, the advertisers are prepared to screen and manage utilitarian practices with the implementation and utilization of cloud information.…”
Section: Diffusion Of Innovation Theorymentioning
confidence: 99%